Solution for Recording Interfaith Marriages Following Supreme Court Circular (SEMA) Number 2 of 2023 in Indonesia - Syafrida; Tarigan, Arihta Esther; Suryani, Reni; Warsito (Sinergi International Journal of Law, 2024)
This research aims to explore the solutions for recording marriages following the issuance of Supreme Court Circular (SEMA) Number 2 of 2023. According to the law, a marriage is valid if it meets the cumulative elements of Article 2, paragraphs (1) and (2), which require that it be in accordance with religious and belief systems and recorded according to regulations. Conversely, a marriage is invalid if it does not comply with religious and belief laws, resulting in the inability to register it. Before the issuance of the SEMA, interfaith marriages could be registered at the Civil Registry Office by submitting a registration application to the local District Court. However, after the issuance of this circular, such registration is no longer possible. The research method adopts a normative juridical approach, delving into literature data, particularly legislation. Despite the new regulations, interfaith marriage registrations can still occur, as judges may base their decisions on the Population Administration Law rather than the Marriage Law. Article 56, paragraph (1) of the Marriage Law essentially requires Indonesian citizens to comply with the marriage law, leaving no room for interfaith marriages. Therefore, to prevent registrations by judges at all court levels, it is necessary to reconstruct the Population Administration Law and require that one of the parties adheres to the religion and/or beliefs of their partner.